Language and Linguistics in a Complex World - Busse, Beatrix; Dumrukcic, Nina; Kleiber, Ingo (Diskursmuster / Discourse Patterns, 2023)
This collection of papers addresses methodological issues in corpus linguistics and recent trends in the field. The authors discuss the multitude of data types that can be collected for computational analysis, tracing grammatical features from a diachronic perspective, how corpora can be used to observe discourse patterns in the press and other mediums such as YouTube, and using an interdisciplinary approach to study large compilations of texts.